From intercalation to groove binding: switching the DNA-binding mode of isostructural transition-metal complexes - Ahmad, Haslina; Wragg, Ashley; Cullen, Will; Wombwell, Claire; Meijer, Anthony J. H. M.; Thomas, Jim A. (Wiley-VCH Verlag, 2014)
The interaction with duplex DNA of a small library of structurally related complexes that all contain a d6-metal ion coordinated to either the 2,2′:4,4′′:4′,4′′′-quaterpyridyl ligand or its methylated derivative are reported. This library is made up of a mixture of newly synthesised and previously reported systems. Despite their structural similarities the complexes display an almost 20-fold variation in binding affinities. Although effects due to the overall charge of the complexes are apparent, the differences in binding characteristics are deeper than this; indeed, in a number of cases, changes in overall charge have little effect on binding affinity. Intriguingly, despite interacting with DNA through unfused ring systems, although two of the complexes studied are groove binders, the majority are non-classical intercalators. A rationale for these effects has been obtained through a combination of experimental and computational studies.